Розробка розрахункових моделей питомих витрат магнію та вмісту сірки в чавуні для управління процесом інжекційної десульфурації чавуну - Шевченко, Анатолій Пилипович; Маначин, Іван Олександрович; Двоскін, Борис Вульфович; Башмаков, Олександр Михайлович; Рибальченко, Марія Олександрівна (Український державний університет науки і технологій, ІВК «Системні технології», Дніпро, 2024)
UKR: Метою роботи є надійний прогноз та розрахунок необхідних витрат магнію з різних умов – вихідного вмісту сірки, маси чавуну та заданого кінцевого вмісту сірки для забезпечення скорочення витрат десульфураторів. Крім того важливим є прогнозування поточного вмісту сірки в чавуні залежно від витрат магнію для підвищення надійності досягнутих вмістів сірки в розплаві чавуну. Проведені розробки дозволили отримати розрахункові моделі для оцінки закономірностей процесів позапічної десульфурації чавуна моноінжекцією зернистого магнію для оцінки витрат магнію для діючих та новозбудованих потужностей з десульфурації чавуна в ковшах різного розміру (40-350 т) при різних початкових вмістах сірки в чавуні (0,02-0,07 %) і вимогах до кінцевого вмісту сірки в чавуні (≤0,002-0,015 %) для застосування у АСУ процесом позапічної обробки чавуну.

ENG: Built and put into operation experimental industrial and industrial installations and cast iron desulfurization departments ensured a reduction of sulfur content in cast iron to 0.005-0.010% in industrial conditions. The purpose of the work is to reliably predict the calculation of the necessary consumption of magnesium from various conditions - the initial sulfur content, the mass of cast iron and the given final sulfur content to ensure the reduction of desulfurization costs. In addition, it is important to predict the current content of sulfur in cast iron depending on the consumption of magnesium in order to increase the reliability of the achieved content of sulfur in molten iron. The developments carried out to assess the regularities of the processes of out-of-furnace desulfurization of cast iron by monoinjection of granular magnesium made it possible to obtain calculation models for the assessment of existing and newly built capacities for desulfurization of cast iron in ladles of different sizes (40-350 t) at different initial sulfur contents in cast iron (0.02-0.07 %) and requirements for the final content of sulfur in cast iron (≤0.002-0.015%). Calculation models are presented.
Development of Calculation Models of Specific Magnesium Сonsumption and Sulfur Content in Cast Iron to Control the Process of Injection Desulfurization of Cast Iron
І. Маначин: ORCID 0000-0001-9795-6751; М. Рибальченко: ORCID 0000-0001-5162-5201
Keywords: десульфурація; чавун; ківш; моделі; витрата магнію; desulfurization; cast iron; ladle; models; magnesium consumption; КАВП; TECHNOLOGY::Chemical engineering::Metallurgical process and manufacturing engineering